Investigating the role of Cten in metastatic colorectal cancer - Thorpe, Hannah (2016)
Cten is upregulated in a number of tumour types and in colorectal cancer (CRC), expression is associated with advanced stage, poor prognosis and distant metastasis. Cten appears to regulate cell motility and it can confer features of stemness although, the knowledge of underlying signalling mechanisms is sparse. Cten is localised at focal adhesions and in the nucleus. It may promote cell motility through the regulation of cell adhesion and it may confer stemness through gene activation. To determine the biological activity of Cten in CRC, this thesis investigated three areas of Cten signalling.